2020
DOI: 10.3390/pathogens9060418
|View full text |Cite
|
Sign up to set email alerts
|

A Post-Haustorial Defense Mechanism is Mediated by the Powdery Mildew Resistance Gene, PmG3M, Derived from Wild Emmer Wheat

Abstract: The destructive wheat powdery mildew disease is caused by the fungal pathogen Blumeria graminis f. sp. tritici (Bgt). PmG3M, derived from wild emmer wheat Triticum dicoccoides accession G305-3M, is a major gene providing a wide-spectrum resistance against Bgt. PmG3M was previously mapped to wheat chromosome 6B using an F6 recombinant inbred line (RIL) mapping population generated by crossing G305-3M with the susceptible T. durum wheat cultivar Langdon (LDN). In the current study, we aimed to explore the defens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…However, it has been reported that PmG3M is derived from an T. dicoccoides introgression (Xie et al, 2012 ). It was also recently investigated functionally and shown to provide a post-haustorial defense mechanism (Wei et al, 2020 ). The other reported genes for Chr6B tend to map to the short arm of Chr6B ( Pm11, Pm12, Pm20 , and Pm07j126 ) or in the case of Pm27 143,716,930 bp downstream of MTA37.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that PmG3M is derived from an T. dicoccoides introgression (Xie et al, 2012 ). It was also recently investigated functionally and shown to provide a post-haustorial defense mechanism (Wei et al, 2020 ). The other reported genes for Chr6B tend to map to the short arm of Chr6B ( Pm11, Pm12, Pm20 , and Pm07j126 ) or in the case of Pm27 143,716,930 bp downstream of MTA37.…”
Section: Discussionmentioning
confidence: 99%
“…1a-d). The same post-haustorium resistance mechanism has also been found in WEW accession G305-3M which contains PmG3M (Wei et al 2020). Most Pm genes cloned so far are induced by Bgt at different time points from 6 to 48 hpi, such as Pm5e , Pm41 (Li et al 2020), Pm21 (He et al 2018), Pm2 (Chen et al 2019), and Pm24 (Lu et al 2020.…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, since WEW is an excellent source for other disease resistance genes/alleles, in future breeding program we propose to pyramid several such genes from WEW and transfer them into durum and bread wheat varieties to obtain more durable resistance to different diseases. These genes can include powdery mildew resistance genes PmG16 and PmG3M (Xie et al 2012;Wei et al 2020), and the broad spectrum yellow rust resistance genes from WEW, such as Yr15 (Klymiuk et al 2018) andYr36 (Fu et al 2009). Altogether, the results of our study demonstrate that WEW is a valuable genetic resource for improving disease resistance in wheat cultivars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pm69 (PmG3M ), identified from WEW accession G305-3M, is a dominant gene conferring a wide-spectrum resistance to Bgt isolates from around the globe 38 . Pm69 is the only gene derived from WEW that was mapped to the telomeric region of chromosome arm 6BL 36,38,39 .…”
Section: Introductionmentioning
confidence: 99%